2022
DOI: 10.3390/nano12234289
|View full text |Cite
|
Sign up to set email alerts
|

N, S Co-Doped Carbons Derived from Enteromorpha prolifera by a Molten Salt Approach: Antibiotics Removal Performance and Techno-Economic Analysis

Abstract: N, S co-doped bio-carbons with a hierarchical porous structure and high surface area were prepared using a molten salt method and by adopting Entermorpha prolifera (EP) as a precursor. The structure and composition of the bio-carbons could be manipulated by the salt types adopted in the molten salt assisted pyrolysis. When the carbons were used as an activating agent for peroxydisulfate (PDS) in SMX degradation in the advanced oxidation process (AOP), the removal performance in the case of KCl derived bio-carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Molten-salt-assisted carbonization, which employs a molten inorganic salt as the medium, has emerged as an important complementary route to the carbonization strategy for the synthesis of biomass-derived CS-SACs. 60–62 Despite the previously mentioned biomass complexation effect that can alleviate metal sintering to a certain degree, the eventual development of metal clusters or nanoparticles is unavoidable. Of course, these phenomena also explain why post-treatment procedures such as acid etching are used as a routine procedure in carbonization-based routes.…”
Section: Synthetic Strategies For Biomass-derived Cs-sacsmentioning
confidence: 99%
“…Molten-salt-assisted carbonization, which employs a molten inorganic salt as the medium, has emerged as an important complementary route to the carbonization strategy for the synthesis of biomass-derived CS-SACs. 60–62 Despite the previously mentioned biomass complexation effect that can alleviate metal sintering to a certain degree, the eventual development of metal clusters or nanoparticles is unavoidable. Of course, these phenomena also explain why post-treatment procedures such as acid etching are used as a routine procedure in carbonization-based routes.…”
Section: Synthetic Strategies For Biomass-derived Cs-sacsmentioning
confidence: 99%
“…Carbon-based materials represent a group of important raw materials for different industries. Duo to their high electroconductivity and high thermal and chemical stability, as well as bio-compatibility, many types of carbon materials, such as graphene or reduced graphene oxides [4][5][6][7][8][9][10][11][12][13][14][15], carbon fibers [16][17][18], carbon dots [19], active carbons [20][21][22] and biomass-derived carbons [23][24][25][26][27][28][29][30][31][32], have been deliberately prepared for different application aims. Biomass has many definitions, such as biodegradable products, wastes and residues from agriculture, forestry and related industries, including fisheries and aquaculture, as well as biodegradable parts of industrial and municipal wastes.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the performance of potassium-chloride-derived biochar was better than that of sodium-chloride-derived biochar, and the removal rate reached 99.6% in actual water treatment. Moreover, economic evaluation confirmed that this EP-derived biochar is more competitive than commercial activated carbon in cost, which demonstrates that the EP could be employed as an abundant biowaste that produces bio-carbons with high performances, and the molten salt strategy could be further optimized by adopting low-cost salt to reduce the cost of manufacture [ 3 ]. Based on this concept, Humulus scandens was firstly used as a biomass precursor to prepare biochar through a molten salt method by Bai et al The as-derived biochar exhibited a high specific surface area, abundant oxygen-containing functional groups, and a good adsorption performance for heavy metal ions such as Cu 2+ and Pb 2+ .…”
mentioning
confidence: 99%